Immediate outcomes of treatment of severe mitral annular calcification - R. M. Muratov; M. N. Sorcomov; A. S. Sachkov; S. I. Babenko; A. M. Sleptsova; M. I. Terekhov (Вестник трансплантологии и искусственных органов)
Mitral annular calcification (MAC) is a chronic degenerative process involving the fibrous part of the mitral complex, characterized by calcium deposition and loss of valve function. MAC prevalence is 8–10%, but despite this, the clinical significance of MAC is underestimated. Currently, there are reports that complete decalcification leads to improved long-term outcomes in patients with severe MAC. An analysis of the immediate outcomes of mitral valve surgery in patients with severely calcified mitral annulus with decalcification was performed. The calcified annulus fibrosus underwent complete decalcification in all cases. Calcium deposits were removed in a single block, in 6 cases it was reconstructed with a xeno-pericardial patch; in 2 cases the annulus fibrosus was sutured. There were 2 cases of in-hospital mortality, caused by acute heart failure on day 8 in 1 patient and pulmonary embolism on day 30 after operation in the second patient. There were no complications associated with coronary artery injury and left ventricular posterior wall rupture. Experience in the treatment of severe mitral valve calcification with extensive annulus fibrosus decalcification and subsequent reconstruction is possible and gives satisfactory results.